Kultur i vården på hälsocentraler : Intervjuer om möjligheter och hinder - Vennberg, Berit (2015)
Projects have previously shown that culture can contribute to,and even,promote health (Clift, 2012). Norrbottens läns landsting aims to strengthen the health for people in Norrbotten through culture. The aim of this thesis is to study, through interviews, managers' perceptions of the importance of, and the conditions for, culture in healthcare at health centers in Luleå and Boden and how the information material Kulturhälsoboxen has been received. Kulturhälsoboxen is sent to all health centers in Sweden, but no follow-up has been done. The questions were about which opportunities and obstacles that manager feels about the inclusion of culture in health care. Antonovsky's (1991) model SOC has been used in the interpretation of the interviews.The results showthat the most important thing was,that when something is introduced into the business should this not require too much of the limited resource of time. Kulturhälsoboxen was a surprise to most of theinterviewees.Despite this, many have read or browsed the books and spread them on to their staff. Manyfelt that cultural activities can provide meaningful psychosocial effects for patients. Some wanted more evidence for the health benefits, which always is important in health care. Validerat; 20150626 (global_studentproject_submitter)